Coral Reef Development as an Indicator of Seal Level Fluctuation: A Preliminary Study on Pleistocene Reef in Bulukumba, South Sulawesi - Imran, A. M.; Farida, M.; Arifin, M. F.; Husain, R.; Hafidz, A. (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.1.53-66Pleistocene reefs in eastern part of Indonesia are abundantly found along the coast as raised reef. They express highly tectonized and/or uplifted area characterized by several terraces. Therefore the reef size is narrow. This research is located at Bira District of Bulukumba Regency or it lies at the southern tip of South Sulawesi Peninsula. The objective of this research is to define depositional environment based on coral development. Several methods were applied such as intersect lines which were perpendicular to the cliff, geochemical and petrographic analyses, as well as paleoenvironment interpretation. Three facies are described at the Pleistocene reef, namely 1) Reef Front Facies, 2) Reef Core Facies, 3) Back Reef Facies. Based on facies association and organism accumulation, the depositional environment of Pleistocene reef is interpreted to be developed in a small reef complex on an unstable basement. The reef has experienced at least 3 (three) times of sea level fluctuation.